2022
DOI: 10.1055/s-0042-1748649
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes after Subpectoral Breast Augmentation with Microtextured or Macrotextured Implants Using the BREAST-Q

Abstract: Background Breast augmentation with implants is the most commonly performed cosmetic plastic surgery in Brazil and worldwide. The aim of this study was to assess patient satisfaction and quality of life following subpectoral breast augmentation with either microtextured or macrotextured implants, using the BREAST-Q. Methods A prospective study was conducted with 40 women with hypomastia undergoing subpectoral breast augmentation. The patients were randomly allocated to two groups to receive either mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…As a result, some patients complain about the adverse effects on the quality of their sex life, which is at variance with the very purpose of the BREAST-Q. 13-16 This result was confirmed in the last 6 years of follow-up with our patients. It is likely that most patients have not had to pay minute attention to their breasts, or that most surgeons have ignored it, and thus, we have not followed the literature in this regard to date.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As a result, some patients complain about the adverse effects on the quality of their sex life, which is at variance with the very purpose of the BREAST-Q. 13-16 This result was confirmed in the last 6 years of follow-up with our patients. It is likely that most patients have not had to pay minute attention to their breasts, or that most surgeons have ignored it, and thus, we have not followed the literature in this regard to date.…”
Section: Discussionsupporting
confidence: 76%
“…This dissatisfaction is related to a problem with a negative effect on the BREAST-Q. 13-15 Unfortunately, the complaint has been neglected by surgeons to such an extent that there are no reports in the literature on this subject. All of these suggest that implant breast augmentation needs further improvement.…”
mentioning
confidence: 99%
“…In the authors’ defense, several of the most referenced studies investigating QoL with BREAST-Q after elective cosmetic breast augmentation do not surpass the 6-month mark. 3,4,6,8 These studies all found similarly high positive impact of breast augmentation on satisfaction with breasts, psychosocial well-being, and sexual well-being. Although this study is commendable for including a range of medical centers and surgeons, allowing for a large number of participants, there is lacking a universally consistent technique and information related to how implant size or adverse events might impact patient-reported satisfaction with outcome, physical discomfort in particular.…”
mentioning
confidence: 80%
“…2 Luong et al found, like in other studies, that physical well-being suffered relative to baseline at the study endpoint of 6 months. [3][4][5][6] It was hypothesized that patients tolerate some discomfort in exchange for significant gains in appearance and psychosocial and sexual well-being.…”
mentioning
confidence: 99%
“…45 However, these have a higher capsular contracture rate and risk of bottoming out. 46 In this study, all of our patients after the initial consultation chose textured implants and signed an informed consent including that these have been associated with BIA-ALCL (incidence rate is 0.33 per 1 million person-years in textured implants that use a negative-imprint stamping technique for texturization 43 ).…”
Section: Discussionmentioning
confidence: 99%